If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + -57 = 132 + -3x Reorder the terms: -57 + -12x = 132 + -3x Solving -57 + -12x = 132 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -57 + -12x + 3x = 132 + -3x + 3x Combine like terms: -12x + 3x = -9x -57 + -9x = 132 + -3x + 3x Combine like terms: -3x + 3x = 0 -57 + -9x = 132 + 0 -57 + -9x = 132 Add '57' to each side of the equation. -57 + 57 + -9x = 132 + 57 Combine like terms: -57 + 57 = 0 0 + -9x = 132 + 57 -9x = 132 + 57 Combine like terms: 132 + 57 = 189 -9x = 189 Divide each side by '-9'. x = -21 Simplifying x = -21
| 2+x+4=12 | | 3p-6=10-2m | | -12x-12=-11x+9 | | -4x=0.8 | | N/2-9=-9 | | -31+x=4x+20 | | -4+10+6x=28 | | -12+8x=6x+28 | | 3/6=g/90 | | 6n^2-45n+84=0 | | -5x-39=57+x | | -18p=-9 | | xx+1=0 | | 4lnx=60 | | -34+9x=6x+53 | | -4=-16x | | 7/8=n | | -29-10x=-12x+25 | | 37=5p-3 | | -152-x=8x+55 | | 10x+19=3x+229 | | 10x+19=3x+22 | | -82-12x=-5x+65 | | 48=4n+20 | | x+6=4x^2-12x+9 | | -101-3x=-10x+39 | | -95+12x=6x+31 | | Y^2=14y-48 | | =2x+2 | | -39+6x=10x+17 | | 47=5m+2 | | 14+1/5=10 |